PENGARUH PROFITABILITAS, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP KEBIJAKAN DIVIDEN PADA PERUSAHAAN SEKTOR TRADE, SERVICE DAN INVESTEMENT YANG TERDAFTAR DI BEI PERIODE 2016-2020 - YUda Iswanda; Anggri Pratama Nasution (Ensiklopedia Education Review, 2021)
Investing decisions are heavily influenced by the company's dividend policy, making it an important component to study. As part of the research, we'll look at how profitability affects dividend policy in publicly traded trade and service sector companies listed on the IDX throughout the 2016-2020 timeframe and how firm size affects dividend policy. The statistical analysis was carried out using the multivariate linear regression approach. Findings from this study reveal that a company's return on equity (ROE) has no influence on its payout policy while it is listed on the IDX between 2016 and 2020 based on these findings. The current ratio variable has a statistically significant and statistically significant effect on the dividend policy of businesses listed on the IDX. In firms that are traded, serviced, and invested in on the IDX, it has a substantial impact on dividend policy between 2016 and 2020 Return on equity (ROE), C:R and L:L all account for 40.9 percent of dividend policy influence in trade, service and investment sector companies that are listed on the IDX exchange. We didn't give it a second thought during this inquiry.Keywords : ROE, CR, SIZE, DPR.